DEVELOPING ENGLISH WRITING MATERIALS OF DESCRIPTIVETEXT FOR TENTH GRADE STUDENT BASED ON PROJECT BASED LEARNING AT SMA SWASTA MARISI MEDAN - Winda Sundari; Rahmad Husein; Rika Rika (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2018)
This research aimed to find out the target and learning needs of Grade X SMA SWASTA MARISI MEDAN. Moreover, it had a goal to develop English materials for learning writing skills. This is a research and development (R&D) study. The subjects of this research were 25 students of Grade X SMA SWASTA MARISI MEDAN. The need analysis data were collected by using questionnaires and an interview. Then, the results of questionnaires were calculated through percentage. Thus, the highest percentage was considered as the needs of students. Meanwhile, the results of expert judgment were analyzed in the form of descriptive statistics. Three units of materials were developed in this research. Each unit consists of introduction, main lesson and reinforcement. These materials used Project-Based  Learning as the approach in learning writing skill. The units covered some tasks as identify the generic structure, write a short paragraph and complete the sentences. Mostly, the themes used represented students’ knowledge about the popular places and person around them. According to the results of the expert judgment, the materials were very relevant to be used for Grade X SMA SWASTA MARISI MEDAN.    Keywords: learning writing, writing, descriptive text